Antithrombin-mediated Inhibition of Factor Vlla-Tissue Factor Complex by the Synthetic Pentasaccharide Representing the Heparin Binding Site to Antithrombin - Claude Lormeau, Jean; Pascal Herault, Jean; Marc Herbert, Jean (Thrombosis and Haemostasis, 1996)
We examined the effect of the synthetic pentasaccharide representing the minimal binding site of heparin to antithrombin on the antithrombin-mediated inactivation of factor Vila bound to tissue factor. This effect was compared to the effect of unfractionated heparin. Using purified recombinant human coagulation factors and either a clotting or an amidolytic assay for the determination of the residual activity of factor Vila, we showed that the pentasaccharide was an efficient antithrombin-dependent inhibitor of the coagulant activity of tissue factor-factor Vila complex. In our experimental conditions, assuming a mean MW of 14,000 for heparin, the molar pseudo-first order rate constants for ATIII-mediated FVIIa inhibition by ATIII-binding heparin and by the synthetic pentasaccharide were found to be similar with respective values of 104,000 ± 10,500 min-1 and 112,000 ± 12,000 min-1 (mean ± s.e.m., n = 3)